Covid 19 Pandemic: Moderating Panic Buying Behavior to Impulse Buying - Ahmad Ismoyo Dwi Sapto Aji; M. Trihudiyatmanto (Jamasy: Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2022)
Purpose – This study aims to determine the effect of panic buying on impulse buying and during the COVID-19 pandemic as a variable that moderates the effect of panic buying on impulse buying. Unexpected purchases during the COVID-19 pandemic are sometimes caused by panic buying behavior by consumers. Method – In this study using a sample of 100 respondents with the criteria of respondents being taken by researchers as samples are consumers who have visited directly and bought products at the Alfamart Karang Tengah Store, Banjarnegara at least once and at least 17 years old. Sampling of respondents was carried out by purposive sampling. The regression model hypothesis testing in this study used an interaction test or Moderated Regression Analysis (MRA). Results – The results show that during the COVID-19 pandemic, panic buying behavior increased, resulting in an increase in impulse buying. Implications – useful as a guide for determining business policies and strategies during the pandemic.